2008
DOI: 10.1002/anie.200800266
|View full text |Cite
|
Sign up to set email alerts
|

Filamentous Artificial Virus from a Self‐Assembled Discrete Nanoribbon

Abstract: Therapeutic viruses: A filament‐shaped artificial virus is formed by using a preorganized supramolecular nanoribbon as a template. The artificial virus (see picture), which is composed of the nanoribbon, small interfering RNAs (blue, double‐helix shape), and hydrophobic guests (red), is highly efficient in delivering genes and drugs to the inside of cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 34 publications
0
56
0
Order By: Relevance
“…Cationic polymers-such as linear-and branched-polyethylenimine (PEI), polyamidoamine (PAMAM) dendrimer, poly-L-lysine, cationic polyesters (Lim et al, 2001(Lim et al, , 2000, and poly-β-amino esters-have been the subject of intensive interest as nonviral genecarrier molecules. Because the polyanionic nature of nucleic acids inhibits them from crossing the same charged cytoplasmic membrane barrier, cationic polymers are used to neutralize the negative charges of nucleic acids (Lim et al, 2008).…”
Section: R E S E a R C H A R T I C L Ementioning
confidence: 99%
“…Cationic polymers-such as linear-and branched-polyethylenimine (PEI), polyamidoamine (PAMAM) dendrimer, poly-L-lysine, cationic polyesters (Lim et al, 2001(Lim et al, , 2000, and poly-β-amino esters-have been the subject of intensive interest as nonviral genecarrier molecules. Because the polyanionic nature of nucleic acids inhibits them from crossing the same charged cytoplasmic membrane barrier, cationic polymers are used to neutralize the negative charges of nucleic acids (Lim et al, 2008).…”
Section: R E S E a R C H A R T I C L Ementioning
confidence: 99%
“…Nonetheless, Lim et al were able to synthesize a self-assembling filamentous capsid containing siRNA by using self-assembling β-sheet peptides with poly-lysine sequences for DNA binding and covalently attached glucose ligands for cell-specific receptor binding. This synthetic capsid was able to deliver siRNA and silence GFP expression in HeLa cells just as well as lipofectamine (∼70% reduction in GFP expression) [36]. Malay et al also showed that gold nanoparticles could be used to catalyze formation of capsids with cysteine rich trp RNA-binding attenuation protein (TRAP) monomers.…”
Section: Highly Evolved Hgt: Virusesmentioning
confidence: 99%
“…Students were informed that the corporations were all competing for a grant that would be awarded to the most promising artificial virus. The work students completed in the course was not simply a theoretical exercise; they were investigating an issue with significant real-world implications (23).…”
Section: Project Description and Assessmentmentioning
confidence: 99%